Use the method of variation of parameters to solve the system
𝑋′ =[
3 −1 −1
−2 3 2
4 −1 −2
]𝑋+[
1
𝑒𝑡
𝑒𝑡]
The given question is not at all clear. So, I am taking a example and solving that.
Question: Find a particular solution of:
"\\mathbf{y}^{\\prime}=\\left[\\begin{array}{ccc}\n2 & -1 & -1 \\\\\n1 & 0 & -1 \\\\\n1 & -1 & 0\n\\end{array}\\right] \\mathbf{y}+\\left[\\begin{array}{c}\ne^{t} \\\\\n0 \\\\\ne^{-t}\n\\end{array}\\right]"
Solution:
The characteristic polynomial of the coefficient matrix is
"\\left|\\begin{array}{lll}\n2-\\lambda & -1 & -1 \\\\\n1 & -\\lambda & -1 \\\\\n1 & -1 & -\\lambda\n\\end{array}\\right|=-\\lambda(\\lambda-1)^{2}"
"\\mathbf{y}_{1}=\\left[\\begin{array}{l}\n1 \\\\\n1 \\\\\n1\n\\end{array}\\right],\\quad \\mathbf{y}_{2}=\\left[\\begin{array}{l}\ne^{t} \\\\\ne^{t} \\\\\n0\n\\end{array}\\right],\\quad \\text { and } \\quad \\mathbf{y}_{3}=\\left[\\begin{array}{l}\ne^{t} \\\\\n0 \\\\\ne^{t}\n\\end{array}\\right]"
are linearly independent solutions.
"Y=\\left[\\begin{array}{lll}\n1 & e^{t} & e^{t} \\\\\n1 & e^{t} & 0 \\\\\n1 & 0 & e^{t}\n\\end{array}\\right]" is a fundamental matrix. We seek a particular solution
"\\mathbf{y}_{p}=Y \\mathbf{u}" where "Y \\mathbf{u}^{\\prime}=\\mathbf{f}" ; that is:
"\\left[\\begin{array}{lll}\n1 & e^{t} & e^{t} \\\\\n1 & e^{t} & 0 \\\\\ne & 0 & e^{t}\n\\end{array}\\right]\\left[\\begin{array}{l}\nu_{1}^{\\prime} \\\\\nu_{2}^{\\prime} \\\\\nu_{3}^{\\prime}\n\\end{array}\\right]=\\left[\\begin{array}{l}\ne^{t} \\\\\n0 \\\\\ne^{-t}\n\\end{array}\\right]"
The determinant of "Y" is the Wronskian:
"\\left|\\begin{array}{lll}\n1 & e^{t} & e^{t} \\\\\n1 & e^{t} & 0 \\\\\n1 & 0 & e^{t}\n\\end{array}\\right|=-e^{2 t}"
Thus, by Cramer's rule,
"\\begin{aligned}\nu_{1}^{\\prime} &=-\\frac{1}{e^{2 t}}\\left|\\begin{array}{lll}\ne^{t} & e^{t} & e^{t} \\\\\n0 & e^{t} & 0 \\\\\ne^{-t} & 0 & e^{t}\n\\end{array}\\right| &=-\\frac{e^{3 t}-e^{t}}{e^{2 t}}=e^{-t}-e^{t} \\\\\nu_{2}^{\\prime} &=-\\frac{1}{e^{2 t}}\\left|\\begin{array}{ccc}\n1 & e^{t} & e^{t} \\\\\n1 & 0 & 0 \\\\\n1 & e^{-t} & e^{t}\n\\end{array}\\right| &=-\\frac{1-e^{2 t}}{e^{2 t}}=1-e^{-2 t}\n\\end{aligned}"
"u_{3}^{\\prime}=-\\frac{1}{e^{2 t}}\\left|\\begin{array}{ccc}\n1 & e^{t} & e^{t} \\\\\n1 & e^{t} & 0 \\\\\n1 & 0 & e^{-t}\n\\end{array}\\right|=\\frac{e^{2 t}}{e^{2 t}} \\quad=1"
Therefore
"\\mathbf{u}^{\\prime}=\\left[\\begin{array}{l}\ne^{-t}-e^{t} \\\\\n1-e^{-2 t} \\\\\n1\n\\end{array}\\right]"
Integrating and taking the constants of integration to be zero yields
"\\mathbf{u}=\\left[\\begin{array}{l}\n-e^{t}-e^{-t} \\\\\n\\frac{e^{-2 t}}{2}+t \\\\\nt\n\\end{array}\\right] \\\\\n \n\n \n\\mathbf{y}_{p}=Y \\mathbf{u}=\\left[\\begin{array}{lll}\n1 & e^{t} & e^{t} \\\\\n1 & e^{t} & 0 \\\\\n1 & 0 & e^{t}\n\\end{array}\\right]\\left[\\begin{array}{l}\n-e^{t}-e^{-t} \\\\\n\\frac{e^{-2 t}}{2}+t \\\\\nt\n\\end{array}\\right]=\\left[\\begin{array}{c}\ne^{t}(2 t-1)-\\frac{e^{-t}}{2} \\\\\ne^{t}(t-1)-\\frac{e^{-t}}{2} \\\\\ne^{t}(t-1)-e^{-t}\n\\end{array}\\right]" is a particular solution.
Comments
Leave a comment